FENOMENA DEIKSIS DAN KESANTUNAN DALAM BAHASA BATAK ANGKOLA-MANDAILING - Pulungan, Alpi Anwar (University of Brawijaya, 2023)
Politeness in the Angkola-Mandailing Batak language is related to personal and social deixis, especially partuturon. This study aims to describe the types of deixis and their application in daily communication and their relation to language politeness. This research is a qualitative research with an ethnographic model of communication and supported by deixis theory. The data sources for this research are the people of Tolang Julu village, Sayur Matinggi, South Tapanuli, North Sumatra. The data was collected by using the method of observation and listening to speech engagement. Furthermore, the data of this research are in the form of speeches and expressions of society that contain deixis in daily communication. The results of this study found five types of deixis, namely personal deixis, social deixis, place deixis, time deixis and discourse deixis. These deixis have many and complex variations, thus proving that the Angkola-Mandailing Batak language is a difficult language to learn. After being investigated, there are two levels of language in the Angkola-Mandailing Batak language, namely somal (rough) and andung (smooth) language. By mastering partuturon (natutu martutur) and andung language (namalo marbaso), one will arrive at the highest politeness in the Angkola-Mandailing Batak language.